Analisis Pengaruh Inovasi Produk, Keberlanjutan Lingkungan, dan Pemasaran Digital terhadap Kinerja Perusahaan: Kasus Unilever Indonesia - Sri Ayu Rahmawati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This study aims to analyze the impact of product innovation (X1), environmental sustainability (X2), and digital marketing (X3) on company financial performance (Y), focusing on Unilever Indonesia. Environmentally friendly and sustainable product innovation, optimal digital marketing strategies, and commitment to environmental sustainability are believed to significantly affect the improvement of the company’s financial performance. The data used in this study were obtained from the company's annual reports and internal surveys, covering relevant financial indicators. The results of this study are expected to provide insights for Unilever Indonesia in formulating long-term strategies that can improve the overall performance of the company.